The “HeForshe” Approach Model to The Elimination of Violence Against Women and Children - Awang, Mariana Ngundju; Huru, Matje M; Namandjabar, Odi; Woda, Wilhelmina A A (JURNAL INFO KESEHATAN, 2023)
The pandemic causes the risk of gender-based violence to increase, one of which is domestic violence. It is because many women as mothers are workers, so they also have to do waiting office tasks, as well as do household work which is frequently burdened by women. Based on data from the Online Information System for the Protection of Women and Children (understood as Sistem Informasi Online Perlindungan Perempuan dan Anak/SIMFONI PPA) in October 2022, 19,613 cases of violence occurred, with details of 3,164 male victims and 17,960 victims, specifically for NTT (East Nusa Tenggara) Province as many as 895 cases of violence. Percentage of Women Victims of Violence by Type of Violence in the Province of NTT of abuse 44.03%, humiliation 65.01%, harassment 7.12%, neglect 12.71%, and others 13.02%. Perpetrators 68.85% are parents and victims of violence against women 1.91% in rural areas and 2.23 in urban areas. The Research Objective is to identify the 'HeForShe'' Approach Model to the Involvement of Men in the Elimination of Violence against Women and Children in Kupang City and Kupang Regency, NTT Province in 2022. The research Method is a Mixed Method, Qualitative with Phenomenological Method and Quantitative Descriptive Survey Method. The population in the study were informants encompassing married men and women aged <55 years with the sample criteria being wife/husband status, and living together for more than 1 year. Female and male aged 18 years and unmarried, living with their parents. Religious leaders, midwives, teachers, and local government. Purposive sampling. Collecting data was performed by in-depth interviews and FGD in groups of 10-15 people, analysis was carried out descriptively, and a way ANOVA test to compare the three models. Research Results: From the 3 proposed models, it was discovered that 65 percent of respondents agreed with model 2, and the results of the one-way ANOVA test were obtained the p-value is 0.002 or smaller than alpha 5%, Conclusion: One model was obtained, namely the Network Coordination Model for the Office of Health, Education and Local Government in Empowering Youth in Primary Health Units and schools in Action to Prevent Violence against Women and Children. Recommended as one of the HeForShe models that is more appropriate to apply in the case of the Approach to the Elimination of Violence Against Women and Children by involving teenagers.